2022
DOI: 10.3390/ijms23094850
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Histological Effects of Glyphosate on Testicular Tissue of the Lizard Podarcis siculus

Abstract: The expansion of agriculture produces a steady increase in habitat fragmentation and degradation due to the increased use of pesticides and herbicides. Habitat loss and alteration associated with crop production play an important role in reptile decline, among which lizards are particularly endangered. In this study, we evaluated testicular structure, steroidogenesis, and estrogen receptor expression/localization after three weeks of oral exposure to glyphosate at 0.05 and 0.5 μg/kg body weight every other day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…More recently, it has been demonstrated that the herbicide glyphosate has negative effects on P. siculus spermatogenesis at both molecular and histological levels [ 59 ]. In detail, oral exposure to glyphosate alters the expression of estrogen receptors in a dose-dependent manner, in particular by increasing the level of estrogen receptors’ transcripts, especially ERβ .…”
Section: Impairment Of Spermatogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been demonstrated that the herbicide glyphosate has negative effects on P. siculus spermatogenesis at both molecular and histological levels [ 59 ]. In detail, oral exposure to glyphosate alters the expression of estrogen receptors in a dose-dependent manner, in particular by increasing the level of estrogen receptors’ transcripts, especially ERβ .…”
Section: Impairment Of Spermatogenesismentioning
confidence: 99%
“…The absence of connexin 43 results in a disruption of the seminiferous epithelium, characterized by the presence of holes between the germ cells that aggregate forming structures termed rosettes. The authors also demonstrated that glyphosate induces the deposition of connective tissue between the seminiferous tubules, leading to fibrosis [ 59 ] ( Figure 3 ), a process observed also in the liver of the same lizards exposed to glyphosate [ 60 ].…”
Section: Impairment Of Spermatogenesismentioning
confidence: 99%
“…The severe liver fibrosis, the activation of the antioxidant defence machinery, and the xenoestrogenic effects of Gly in P. siculus [ 24 ] prompted a broadening of the investigations into reproductive toxicity. In males, Gly altered testicular morphology, affected spermatogenesis, and changed the localization of estrogen receptors in germ cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spermatogenesis involves several important events, including differentiation of primordial germ cells [ 4 , 5 ], signaling between germ and Sertoli cells [ 6 , 7 ], and substitution of histones by protamines after meiosis [ 8 , 9 , 10 ]. These physiological processes can be affected by a large number of exogenous agents that include heavy metals, phthalates, bisphenol-A, polychlorinated biphenyls, dioxins and pesticides, among other xenobiotics [ 11 , 12 , 13 ]. In many developed countries, there is increasing concern regarding the adverse effects of pesticide exposure on human reproduction [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%